Clinical effects of systemic and topical tetracycline therapy on chronic periodontal disease. - Cristiane Gonçalves; Rosa Maria J. Rodrigues; Eduardo Jorge Feres-Filho; Ana Paula Colombo (Universidade Estadual de Campinas, 2015)
In order to evaluate the additional effects of antimicrobials associated with conventional therapy, this study compared the clinical changes in subjects treated with scaling and root planing (SRP) alone or in combination with local or systemically administered tetracycline over time. Thirty patients with chronic periodontitis were randomly assigned to 3 groups: SRP + 500 mg of systemic tetracycline twice/day for 14 days (SRP + Tetra); SRP alone and SRP + tetracycline fibers at 4 selected sites for 10 days (SRP + Fiber). Clinical assessments were made at 6 sites/tooth at baseline, 3 and 6 months post-therapy. Two types of analyses were performed, one including all sites and other only the 4 test sites in each subject. Significant changes within and between groups were sought using Friedman, Mann-Whitney and Kruskal-Wallis tests. All therapies resulted in clinical improvement over time, which was more marked in the groups treated with tetracycline. The SRP + Tetra group had a significant lower % of sites with plaque, bleeding on probing (BOP) and deep probing pocket depth (PPD) at 3 months; higher % of sites with shallow PPD and lower % of sites with PPD = 4 - 6mm at 3 and 6 months compared to SRP alone (p < 0.05). Subjects in the SRP + Fiber group had a significant lower % of sites with BOP at 3 months and lower mean of attachment level at 6 months than the controls (p < 0.05). The adjunctive use of systemic or local tetracycline may improve the efficacy of the mechanical non-surgical therapy of chronic periodontitis.